1998
DOI: 10.1111/j.1423-0410.1998.tb05454.x
|View full text |Cite
|
Sign up to set email alerts
|

The French Hæmovigilance System

Abstract: Haemovigilance was part of the reform of the French transfusion system. The haemovigilance network is now operational with approximately 4600 transfusion incidents reported annually. Immediate incidents observed within 8 days after transfusion account for 85% of the reports. A cause cannot be identified in 41% of these, usually concerning minor clinical incidents with transient fever and/or shivers. An allergic reaction is described in 31% of transfusion reactions. Immunological conflicts account for 18% and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 0 publications
0
28
0
1
Order By: Relevance
“…2 The overall goal is to make clinical care safer for patients requiring transfusion and to demonstrate to the public, patients and professionals, the safety of existing transfusion systems. 3 It can be approached in a number of different ways, as illustrated by the variety of systems which have been developed in different countries in recent years.…”
Section: What Is Hemovigilance?mentioning
confidence: 99%
See 2 more Smart Citations
“…2 The overall goal is to make clinical care safer for patients requiring transfusion and to demonstrate to the public, patients and professionals, the safety of existing transfusion systems. 3 It can be approached in a number of different ways, as illustrated by the variety of systems which have been developed in different countries in recent years.…”
Section: What Is Hemovigilance?mentioning
confidence: 99%
“…3 It can be approached in a number of different ways, as illustrated by the variety of systems which have been developed in different countries in recent years. 2,4,5 Issues which must be considered when devising a scheme of national hemovigilance or surveillance include the following:…”
Section: What Is Hemovigilance?mentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] In these reports, only the more severe or potentially life-threatening septic reactions are reported. It is the opinion of this author that such reports represent only one end of the clinical spectrum of septic transfusion reactions.…”
Section: Prevalence Of Bacterial Contamination Of Cellular Blood Compmentioning
confidence: 99%
“…2 Similarly, the French hemovigilance system reported that bacterial contamination was responsible for 5 of the 33 deaths attributed to transfusion in 1996 and 1997. 3 In the United States, the bacterial contamination study, known as BaCon, recently provided evidence that septic transfusion reactions also occur regularly in the United States. 4 Although septic transfusion reactions are apparently more common with platelet products, which are stored at 22 ± 2°C, they are also associated with the inadvertent transfusion of bacterially contaminated red blood cells, plasma, cryoprecipitate, and albumin.…”
mentioning
confidence: 99%